A comparative analysis of methods for establishing environmental flows in a Mediterranean watershed: suggestions for management. Issue 4 (16th March 2023) - Baeza Sanz, Domingo; Matías, Aida Gómez
Abstract: In Spain, the largest inter-basin transfer is between the Tagus and Segura Basins. This transfer affects the regimes of the Mundo River, a tributary, and the Segura River. In this study, we examine two methodologies for the calculation of environmental flow regimes for the stretches affected by this alteration. When several methodologies are used to determine environmental flows, difficulty arises in deciding which values to propose to restore the river system hydrologically. This work tries to overcome this problem because we present a proposal to make them complementary. As a method for establishing the validity of minimum flow results, a simulation has been carried out on the river section, which has made it possible to evaluate the habitat created and the possibility of fauna movement. The results obtained by the habitat simulation method exceeded those obtained by hydrological methods in terms of habitat creation and hydraulic conditions for connectivity. These same tests have been used to assess the minimum official proposal made by the water administration. HIGHLIGHTS: A procedure has been established that allows different results of ecological minimum flow values to be used in a complementary way to improve fish habitat. When results obtained by several methodologies are used in a complementary way, a more robust ecological flow regime proposal can be made. The method used can be applied together with other restoration measures in river stretches with strong morphological alterations. Graphical Abstract